A taxonomic revision of the genus Platycranus Fieber, 1870 (Hemiptera: Heteroptera: Miridae: Orthotylinae) - Knyshov, Alexander; Konstantinov, Fedor V. (Zootaxa, 2013)
The Mediterranean orthotyline genus Platycranus is revised. Updated diagnoses and descriptions, data on distribution and hosts are provided for the genus and included species, and a key is presented to facilitate identification of species. Pictures of the dorsal habitus, scanning electron micrographs, and figures of genital structures are given. The following new syn-onymies are established: P. putoni Reuter, 1879 = P. eckerleini Wagner, 1962 = P. jordanicus Linnavuori, 1984; P. metri-orrhynchus Reuter 1883 = P. longicornis Wagner, 1955 = P. rumelicus Simov, 2006; P. remanei Wagner, 1955 = P. minutus Wagner, 1955 = P. orientalis Linnavuori, 1965 = P. jurineae Putshkov, 1985 = P. boreae Gogala, 2002. P. erberi Fieber, 1870 is for the first time reported from Syria, and P. remanei is reported as new to Portugal.